1985
DOI: 10.1128/mcb.5.5.1163
|View full text |Cite
|
Sign up to set email alerts
|

Ethidium bromide-induced loss of mitochondrial DNA from primary chicken embryo fibroblasts.

Abstract: Chicken embryo fibroblasts in uridine-containing medium are inherently resistant to the growth-inhibitory effect of ethidium bromide. The drug was found to inhibit the incorporation of [3lHlthymidine into mitochondrial DNA circular molecules. Mitochondrial DNA was quantitated by DNA-DNA reassociation kinetics with a probe of chicken liver mitochondrial DNA. A mean number of 604 copies of mitochondrial DNA per cell was found. This number decreased progressively in cells exposed to ethidium bromide, and by day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(84 citation statements)
references
References 23 publications
3
80
1
Order By: Relevance
“…The morphological changes were similar to those in cyclosporin-treated cells described by Hojo et al (1999), which were also shown to be more invasive. As shown in Figure 2d, the mtDNA-depleted cells exhibited a markedly slower growth rate as compared to control cells, which is characteristic of r 0 and r 7 cells (Desjardins et al, 1985;King and Attardi, 1989;Miranda et al, 1999). Furthermore, the reverted cells showed a growth rate similar to that of the control cells, suggesting that the altered cell morphology and growth rates are related to the mtDNA content of these cells.…”
Section: Oncogenementioning
confidence: 72%
“…The morphological changes were similar to those in cyclosporin-treated cells described by Hojo et al (1999), which were also shown to be more invasive. As shown in Figure 2d, the mtDNA-depleted cells exhibited a markedly slower growth rate as compared to control cells, which is characteristic of r 0 and r 7 cells (Desjardins et al, 1985;King and Attardi, 1989;Miranda et al, 1999). Furthermore, the reverted cells showed a growth rate similar to that of the control cells, suggesting that the altered cell morphology and growth rates are related to the mtDNA content of these cells.…”
Section: Oncogenementioning
confidence: 72%
“…This death was indicated by the progressive cell detachment from the plates. To confirm that the normal expression of mtDNA was absolutely required for the survival and growth of the 143B.TK Ϫ cells in special DMEM/galactose medium, as suggested by the results described above, mitochondrial protein synthesis was specifically inhibited by adding 40 g/ml chloramphenicol (CAP) to the incubation medium; furthermore, the medium was supplemented with 50 g/ml uridine, since it is known that cells without full mitochondrial gene expression become auxotrophic for pyrimidines (22,36,41).…”
Section: Resultsmentioning
confidence: 99%
“…Influence of culture conditions on the rate of loss of del-mtDNA It has long been recognised that human cells cultured under different conditions are to a different extent dependent on mitochondrial function (Desjardins et al 1985;King and Attardi 1989;Van den Bogert et al 1992). Various cell types cultured in RPMI are highly dependent on mitochondrial function when compared with cells cultured in DMEM; a 50% decline in OXPHOS capacity in RPMI results in cellular dysfunction and a block to cellular proliferation (Van den Bogert et al 1992).…”
Section: Selection Against An Apparently Stable Mtdna Deletion In Peamentioning
confidence: 99%